First record of Gymnogeophagus terrapurpura (Teleostei: Cichliformes) from Argentina - Garcia, Ignacio Daniel (2017)
The genus Gymnogeophagus Miranda Ribeiro 1918 is a diverse genus of geophagin Neotropical cichlids with 1 fossil (Malabarba et al., 2010) and 17 extant species (Malabarba et al., 2015; Loureiro et al., 2016). Species of this genus are endemic to the La Plata basin, the Laguna dos Patos/Merím system, and rio Tramandaí drainage (Malabarba et al., 2015) with one record of G. balzanii in the headwaters of the Guaporé river in the Amazon basin (Lowe-McConnell, 1975). This genus is diagnosed by the presence of a forward-directed spine on top of the first dorsal-fin pterygiophore and by the absence of bony supraneurals (Gosse, 1976). Recently, Gymnogeophagus terrapurpura Loureiro, Zarucki, Malabarba & González-Bergonzoni, 2016 was described as a member of the substrate brooding Gymnogeophagus-rhabdotus-group from the East of the lower Uruguay river basin, the Eastern coastal affluents of the Río de la Plata estuary, and affluents of the Atlantic Ocean in Uruguay. The aim of this work is to report the occurrence of this species in Argentina in tributaries of the Uruguay river near the city of Colón in Entre Ríos province. As part of a revision of the genus Gymnogeophagus from Argentina, we examined existing collection specimens from the San Benito creek and recently collected fresh material from the Perucho Verna and the La Leche creeks, which have been identified as Gymnogeophagus terrapurpura (fig. 1-5).